Girl online : the first novel by Zoella - Sugg, Zoe (New York : Keywords Press, 2016)
Under the alias Girl Online, Penny is a blogger who writes her hidden feelings about boys, high school drama, and friendship, among other topics. She falls in love with Noah, who's secret threatens to ruin Penny's cover and her closest friendship.
Keywords: Blogs -- Fiction; Love stories